Case Report: Dual monoclonal antibody therapy in chronic rhinosinusitis with nasal polyps and severe eosinophilic asthma—a proteome analysis - Blauwblomme, Manon; Gevaert, Philippe; Van Nevel, Sharon; Riemann, Sebastian; Vandewalle, Elke; Holtappels, Gabriele; De Ruyck, Natalie; Derycke, Lara; Eeckels, Anne-Sophie; Vanhee, Stijn; Lambrecht, Bart N.; Brusselle, Guy; et al. (Frontiers in Allergy, 2024)
ContextRecent insights into type 2 inflammation have led to the development of monoclonal antibody therapies for severe asthma and chronic rhinosinusitis with nasal polyps (CRSwNP). Despite add-on therapy with a monoclonal antibody, some individuals remain uncontrolled in terms of upper and/or lower airway symptoms, prompting an exploration of the efficacy of combining biological therapies and their impact on inflammatory pathways.ObjectivesIn this article, we present a distinctive case of a patient with CRSwNP, severe eosinophilic asthma, and uncontrolled upper airway symptoms, who experienced substantial clinical and local inflammatory improvements through dual monoclonal antibody therapy.MethodsWe provide a detailed case description and analysis of the patient's nasal tissue and secretions to gain insights into the local nasal inflammation under this unique therapeutic approach.ResultsThe addition of an anti-IL-4Rα antibody led to an improvement in upper airway symptoms and a reduction in both eosinophilic and neutrophilic inflammation, despite prior anti-IL-5 therapy. These effects were consistently observed in both polyp tissue and nasal secretions.ConclusionOur patient, with CRSwNP, severe eosinophilic asthma, and uncontrolled upper airway symptoms, experienced substantial improvement with dual monoclonal antibody therapy, without major complications or side effects.